Ekofeminisme sebagai Strategi Dekonstruksi Penggambaran Perempuan dalam Novel Matahari Diwan Syams Tabrizi Karya Jalaluddin Rumi - Lestari, Citra Rizky (Jurnal Membaca Bahasa dan Sastra Indonesia, 2022)
The novel Matahari Diwan Syams Tabrizi written by Jalaluddin Rumi writes about many phenomena related to ecology and is associated with the existence of women. In the view of structuralism, these ecofeminism symptoms can be interpreted as a pejorative of the role of women in life, but the deconstruction reads differently. This is also in line with Rumi's goal in writing an article that should not be interpreted as a cliché. This study aims to find deconstructive elements in the novel Matahari Diwan Syams Tabrizi so that new meanings can be found that deconstruct general views. Efforts in this direction can be achieved by uncovering and finding the binary oppositions that exist in the poems in the novel, describing the parallelism of meaning and the meaning field of the existing binary oppositions, then describing the reversal of the hierarchy so as to create a new meaning. The theoretical approach used in this research is poststructuralism and the methodological approach used is binary opposition. Data was collected using heuristic reading techniques, analyzed through hermeneutic reading techniques. The results of this study indicate that there is a paired opposition between birth and death, heaven with earth, and beauty with ugliness. After finding the paired oppositions, then the parallelism of meaning between the oppositions that forms a row of meanings is found, which can then be used as a benchmark to reverse the hierarchy of the existing paired oppositions, so that it becomes a new text or meaning above the previous hierarchy.Keywords: deconstruction, ecofeminism, poetry, novel, poststructural